FEATURES OF FRENCH, AMERICAN AND RUSSIAN INTERCULTURAL INTERACTION - Sedykh, Arkadiy; Ivanishcheva, Olga; Sidorova, Tatyana; Smirnova, Lyubov; Bolgova, Natalia (Revista Inclusiones, 2020)
The article deals with the functioning of cultural stereotypes in French, American and Russian linguistic consciousness. Cross-cultural interaction is interpreted within the framework of mastering linguocultural communication codes and the worldview of allophones. The analysis of factual data is based on the linguosemiotic approach to its interpretation within a discursive utterance. The level of the relevant content of an utterance is interpreted as essential for defining the characterological traits of communication. Other levels are considered during the contrastive description of discourse and complement the essential parameters transmitted by the structure of the ethnocultural code underpinning the creation of utterances in the national language.